Effects of Captivity on the Morphology, Nesting Success, and Growth of the Libyan Falcon (Falco biarmicus) - Dakheel, Husam (Universitas Airlangga, 2025)
Understanding raptor breeding biology is essential for conservation. This study assessed the captive breeding of the Lanner Falcon (Falco biarmicus) and raptor presence in Libya. A pair acquired in 2018 was provided with artificial nests and monitored throughout the 2024 season. Clutch size ranged 4–6 eggs with a 32-day incubation. In 2024, all eggs hatched, producing three fledglings independent after four months. Between 2018–2025, the pair laid 35 eggs, yielding about 25 fledglings, confirming high captive success. Field surveys in October–November 2024 recorded 53 raptors: Falco peregrinus (39; Least Concern), F. biarmicus (6; resident), and Falco cherrug (8; Endangered, migratory). F. peregrinus was the most frequent, with Al Kufrah identified as the main hunting area. Results highlight the effectiveness of captive breeding for Lanner Falcons and underline urgent threats to wild populations, particularly habitat loss and poaching. Strong conservation actions are critical for sustaining both resident and migratory raptors.